Brazilian physical activity guidelines as a strategy for health promotion - Sebastião, Emerson; Schwingel, Andiara; Chodzko-Zajko, Wojtek (Revista de Saúde Pública, 2014)
Public health actions endorsed by the federal government, for instance, health promotion initiatives, usually have greater impact at population level compared to other types of initiatives. This commentary aims to instigate debate on the importance and necessity of producing federally endorsed brazilian physical activity guidelines as a strategy for health promotion.